A two-stage operation optimization model for isolated integrated energy systems with concentrating solar power plant considering multi-energy and multi-type demand response. (November 2022) - Yang, Shenbo; Lin, Hongyu; Ma, Jie; De, Gejirifu; Ju, Liwei; Tan, Zhongfu
Abstract: The isolated integrated energy system coupled with multiple types of energy systems is one of the important ways to guarantee the quality of energy use in remote areas, but due to the lack of external main network's support and random renewable energy output, there is a greater risk of load cutting, which puts forward higher requirements for the operation optimization of the isolated integrated energy system. Therefore, this paper first constructs a two-stage optimization model from both supply and demand side for the linkage development of resources within the isolated integrated energy system. Secondly, an evaluation index system containing economic benefits and system efficiency is constructed to quantify the comprehensive benefits of the two-stage operation optimization. Finally, a remote area in China is selected as the research background for example analysis. The results show that (1) Due to the low matching between supply and demand of the isolated integrated energy system, the unit operation optimization is only conducted from the energy supply side, and the total load shedding is about 101.402 MW. (2) Considering the load side optimization in the first stage, the demand side resources can be mobilized to improve the supply and demand matching degree. Compared with the second stage optimization in Scenario 1, the internal supply rates in Scenarios 2, 3 and 4 are increased by 0.399, 0.159 and 0.567 respectively, and the system net income is increased by 8990, 18840 and 2310 CNY respectively. Limited by factors, such as the subsidy price on the load side, the demand elasticity matrix and the energy selling price on the energy supply side, there is no negative linear relationship between the amount of load shedding and the improvement of energy supplier's economic benefits, so it is necessary to consider actual operation scenarios and reasonably arrange operation and dispatching plans.